The use of digital dental photography in an Eastern European country - Lazar, Radu; Culic, Bogdan; Gasparik, Cristina; Lazar, Camelia; Dudea, Diana (Medicine and Pharmacy Reports, 2021)
Aims. To assess the use of digital photography in dentistry and its relation with the professional experience of the dental practitioners in Romania. Methods. An anonymous questionnaire including eight questions was distributed online to collect information on the use of dental photography. Results. 84.84% of the respondents were using a photographic equipment in their clinical practice. Regarding the type of photographic equipment used, 51.79% of the participants indicated DSLR cameras, 44.05% smartphones, 2.38% compact cameras and 1.78% other devices for taking clinical images. There was a significant association (p<0.05) between the experience of the practitioners and the use of dental photography, type of equipment and protocol used. Conclusions. Respondents with more than 10 years of experience were more likely to use digital photography in their practice than those with less experience. Most of the digital photography users with more than 10 years of experience were taking images with a DSLR Camera (65.52%) followed by 31.04% smartphone users. Conversely, 56.42% of the clinical photography users with less than 5 years of experience mainly preferred a smartphone device and 41.02% a DSLR Camera.